Índice orientador do tratamento sistêmico da gravidez ectópica íntegra com dose única de metotrexato - Elito Junior, Julio [UNIFESP] (1998)
A prospective study was performed with 42 patients with unruptured ectopic pregnancy, which intended to elaborate an index to orient the systemic treatment with the administration of a single intramuscular dose of methotrexate (50 mg/m²). Patients were monitored with beta-hCG titers on days 1, 4 and 7 after the methotrexate. When the titers of beta-hCG declined more than 15%, between days 4 and 7 after methotrexate, the patients were discharged and had an outpatient follow-up monitored with beta-hCG titers weekly until the titers were less than 5 mIU/ml, which represents success of the treatment. We prepared an index for the systemic treatment with methotrexate, with five parameters: (1) initial titers of beta-hCG; (2) aspects of the image at ultrasound (hematosalpinx, gestational sac, live embryo); (3) size of the mass; (4) free fluid in cul-de-sac; (5) collor doppler. Each parameter received a grade from 0 to 2. Grade 0 represented bad prognosis, favorable parameters received grade 2 and borderline parameters received grade one. The success rate with a single dose of methotrexate was 69.0% (29/42). The color doppler was performed in 20 of the 42 patients; in this group of 20 patients the success rate was 75.0% (15/20). In the 22 patients who were not submitted to the color doppler, the average grade of the score in the successful cases was 6.6, and in the unsuccessful it was 3.1. In the group who underwent the doppler (20 patients) the average was 7.9 in the successful cases and 4.2 in the cases that failed. In the present study the cut-off grade was 5, for most of the patients with grades above 5 had a successful treatment (15/16 - 93.75%), while grades equal or below 5 failed. The score will help to indicate the best cases for the medical treatment. We do not advise the treatment when the grade is equal or below 5. Therefore, we can predict a good evolution of the treatment when the grade is above five.